Effect of zinc treatment on growth and phytohormones accumulation in Triticum aestivum L. seedlings priming with abscisic acid - Kosakivska, I.V.; Voуtenko L.V.; Vasjuk, V.A.; Shcherbatiuk, M.M. (Reports of the National Academy of Sciences of Ukraine, 2019)
We investigated whether the priming with abscisic acid (ABA) alters the growth and the content of endogenous phytohormones in winter wheat seedlings under zinc stress. It was shown that zinc at a concentration of 228 mg/l inhibits the growth of the root system. Under these conditions, a decrease in the content of endogenous indole-3-acetic acid (IAA), zeatin, and abscisic acid (ABA) and an increase in gibberellic acid (GA3), isopentenyladenosine (iPA) and salicylic acid (SA) took place. After the adding of 10–6 M ABA to the incubation medium, the growth of seedling roots, the level of stressful hormones ABA and SA became higher. The strategy of the adaptation of wheat seedlings to zinc stress in the presence of exogenous ABA was aimed at the activation of root growth. Changes in the phytohormones balance initiate protective mechanisms and a further adaptation of plants to a high concentration of zinc, and the treatment of grains with exogenous ABA can be used to enhance the stress resistance.